Peningkatan Kemampuan Pemahaman dan Pemecahan Masalah Matematis Siswa Sekolah Menengah Atas dengan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization - Nia Farnika; M. Ikhsan; Hizir Sofyan (Jurnal Elemen, 2015)
Up to now the mathematical ability of students is still relatively low. It is characterized from the low mathematics learning outcomes. Low ability students' mathematical understanding and abilities among students' mathematical problem solving so we need a model of learning that can improve both the mathematical ability. Team Assisted Individualization (TAI) is one type of cooperative learning is expected to increase both these capabilities. This type combines the advantages of cooperative learning and individual learning. This study aims to assess about increasing the understanding and solving mathematical problems high school students with TAI type of cooperative learning model. This study was an experiment that was true experimental research with a quantitative approach. Design research is pretest-posttest control group design. The population in this study was all tenth grade students in the academic year 2013/2014. The sample in this study was two classes, class X1 (control group) and class X2 (experiment group). Data collection was using the test. Data analysis was conducted to gain a score normalized using ANOVA. The results showed that: 1) increased understanding of the mathematical ability of students who obtained using TAI type of cooperative learning model better than students which gained overall in terms of conventional learning and student level (high, medium and low), 2) there was no interaction between learning model and student level (high, medium, and low) to increase the capability of understanding, 3) improving students' mathematical problem solving ability the learning gained by using TAI type of cooperative learning model better than students who received conventional learning was reviewed overall and student level (high, medium and low), and 4) there was interaction between the learning model and student level (high, medium, and low ) to increase problem-solving ability.